CHANGE MANAGEMENT AND ORGANISATIONAL PERFORMANCE IN STARLINE NIGERIA LIMITED (SNL) ABA, ABIA STATE, NIGERIA - Ubah, Chukwudi Nelson; Umeh, Chijioke Sunday; Onyeiwu, Emmanuel Anayo; Nwachukwu, Uzochiamaka Sylvia; Mgbomo, Chinyere Paulina (African Journal of Social and Behavioural Sciences, 2023)
This study focused on change management and organisational performance in Starline Nigeria Ltd Aba, Abia State, Nigeria as case study. The objectives of the study were to determine the extent technological change, leadership change, structural change and policy change affect organisational productivity, patronage, customer retention/acquisition. In line with the objectives, the researchers formulated four research questions and null hypotheses. The work employed descriptive survey research design. The population is 67. Out of 67 copies of the questionnaire distributed, only 65 copies were properly filled and returned. The entire population was used as sample because census method was used. The data collected in this study were analysed using Simple Percentages, Mean Statistics and Pearson Product Moment Correlation Coefficient (PPMCC) at 0.05 level of significance through, Statistical Package for Social Sciences (SPSS version 21.0). The findings revealed that there is a significant relationship between technological change and corporate productivity, structural change enhances customer acquisition, and there is a significant relationship between leadership change and customer retention. Based on the findings, the researchers recommend for effective use of modern technology, regular organisational restructuring, improvements/ implementation of some organisational policies, and leadership changes (when need be) so as to achieve improved productivity, patronage, customer retention and acquisition in the organisations like Starline Nigeria Limited. This study concludes that for organisations to stay relevant and competitive, change is necessary.